A comprehensive and critical analysis of TLS 1.3. Issue 4 (19th May 2022) - Kumari, Noble; Mohapatra, A. K.
Abstract: The TLS 1.3 protocol is a new and an enhanced version of TLS and TLS 1.2 protocols. This protocol assures a secure communication between the client and the server over the internet, that gives an end-to-end security to the seamless cyber-physical system communication. Most of the browsers which have been using TLS 1.2, compromises on several security constraints. In order to address this issue, the TLS 1.3 is defined by the IETF group through multiple improved iterations, which in turn empowers the TLS 1.3 to satisfy complex security requirements for robust communication. According to several research studies, we identified the various scenarios that ascribe the performance of TLS 1.3, its advantage over TLS 1.2 and also the scope of improvement in TLS 1.3 as it is still evolving. As per various research, TLS 1.3 possesses several shortcomings in the areas of Zero Round Trip Time (a.k.a 0-RTT), Fault Tolerance, and Forward Secrecy which leads to security issues. In this paper, we thoroughly examine the shortcoming and scope of improvement in TLS1.3 as presented by various researchers and also study the error alerts defined in it. We propose the requirement of three new error alerts in the current version of TLS 1.3 which are Cookies Extension, Deadlocked Connection and Integrity Algorithm Storage in order to have a smooth communication.